2002
DOI: 10.1002/esp.404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of road building on gully erosion risk: a case study from the Northern Ethiopian Highlands

Abstract: Although obvious in the field, the impact of road building on hydrology and gullying in Ethiopia has rarely been analysed. This study investigates how road building in the Ethiopian Highlands affects the gully erosion risk. The road between Makalle and Adwa in the highlands of Tigray (northern Ethiopia), built in 1993-1994, caused gullying at most of the culverts and other road drains. While damage by runoff to the road itself remains limited, off-site effects are very important. Since the building of the road… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
152
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 207 publications
(172 citation statements)
references
References 21 publications
15
152
0
5
Order By: Relevance
“…Farmers' perception is supported by previous study that states irrespective of the increase in population size, soil and water conservation and land rehabilitation efforts such as enclosures resulted in decreased sheet and rill erosion [27] Besides, studies concluded that increased vegetation density in enclosures result in increased infiltration, that in turn triggers vegetation rehabilitation through superior biomass production thereby improved land productivity including spring discharge [28], [34]. The majorities of respondents are optimistic to the performance of enclosures and reported that enclosures are effective in rehabilitating degraded lands; hence they support vegetation growth on degraded lands.…”
Section: Local Communities' Perception Of Enclosuresmentioning
confidence: 89%
“…Farmers' perception is supported by previous study that states irrespective of the increase in population size, soil and water conservation and land rehabilitation efforts such as enclosures resulted in decreased sheet and rill erosion [27] Besides, studies concluded that increased vegetation density in enclosures result in increased infiltration, that in turn triggers vegetation rehabilitation through superior biomass production thereby improved land productivity including spring discharge [28], [34]. The majorities of respondents are optimistic to the performance of enclosures and reported that enclosures are effective in rehabilitating degraded lands; hence they support vegetation growth on degraded lands.…”
Section: Local Communities' Perception Of Enclosuresmentioning
confidence: 89%
“…With respect to sediment deposition, the volume of a 6-y-old debris fan reached half of the volume of the upslope gully (Nyssen et al, 2002b). Given the presence of an important debris fan in the upper part of the gully system, we estimated that 30% (the coarsest part) of soil lost by gully erosion was trapped in debris fans (239 t y −1 ).…”
Section: Soil Loss and Sediment Movement -The Horizontal View Measurmentioning
confidence: 99%
“…Gully erosion was analysed by the AGERTIM (Assessment of Gully Erosion Rates Through Interviews and Monitoring) method involving measurements and monitoring of gully volumes and detailed interviews on their evolution (Nyssen et al, 2006c), and by use of thresholds for gully initiation, involving slope gradient and drainage area at the position of the gully head (Nyssen et al, 2002b).…”
Section: Measurement and Analysis Of Sediment Redistribution Rates Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Nyssen et al (2002) studied gully development associated with roads in Tigray, Ethiopia by investigating drainage areas, slope, and topographic thresholds similar to Anderson and MacDonald's (1998) work in the Caribbean simulating road erosion contributions. In the wetter, (sub) humid, Amhara region, more discussion is needed concerning the impact of new roads on hydrology.…”
Section: Unpaved Road Contributions In Watershedsmentioning
confidence: 99%